Morphological and physiological components determining yield in native and hybrid corn (Zea mays L.) cultivars in response to density and sowing date. - García-Hernández, Gustavo; Araujo Díaz, Rogelio; Estrada-Campuzano, Gaspar; Martínez-Rueda, Carlos Gustavo; López-Sandoval, José Antonio (Revista Mexicana de Ciencias Agrícolas, 2025)
Grain yield in corn is a function of genotype, agronomic management and environmental conditions where it is grown. The objective of this investigation was to study the impact of planting date and stocking density on grain yield and its components in four maize genotypes for Valles Altos de México. The experiment was carried out in the Toluca Valley, Mexico, during the spring-summer cycle of 2022. Two trilineal cross hybrids: Faisán® and Cherokee® and two native cultivars: "Criollo Blanco and Amarillo Zanahoria", were evaluated under four population densities of 50,000, 60,000, 70,000 and 80,000 plants per ha-1 on three planting dates in March, April and May. On each planting date, the treatments resulting from the possible combinations of genotypes and planting densities were established under a randomized complete block design with four replications. The results showed that the May planting obtained an average grain yield of 6.7 t ha-1. The late planting date increased biomass, harvest index, number of grains per m2, number of grains per ear, plant height and consequently grain yield per m2. Of the 4 genotypes evaluated, the Faisán hybrid had the highest grain yield explained by a greater number of grains per m2. The increase in population density increased grain yield with 80,000 plants ha-1 explained by a higher number of ears per m2. In 2022 the March and April plantings were affected by high temperature and low precipitation, while corn planted in May was not limited by precipitation. The date x cultivar x density interaction revealed the highest grain yield, 8.3 t ha-1, in the May planting with the "Criollo Blanco" cultivar and a density of 80,000 plants ha-1.